Pregnancy Outcome in Relation to Treatment of Murine Typhus and Scrub Typhus Infection: A Fever Cohort and a Case Series Analysis - McGready, Rose (PLoS Negl Trop Dis, 2014)
BACKGROUND: There is a paucity of published reports on pregnancy outcome following scrub and murine typhus despite these infections being leading causes of undifferentiated fever in Asia. This study aimed to relate pregnancy outcome with treatment of typhus. METHODOLOGY/PRINCIPAL FINDINGS: Data were analyzed from: i) pregnant women with a diagnosis of scrub and/or murine typhus from a fever cohort studies; ii) case series of published studies in PubMed using the search terms “scrub typhus” (ST), “murine typhus” (MT), “Orientia tsutsugamushi”, “Rickettsia tsutsugamushi”, “Rickettsia typhi”, “rickettsiae”, “typhus”, or “rickettsiosis”; and “pregnancy”, until February 2014 and iii) an unpublished case series. Fever clearance time (FCT) and pregnancy outcome (miscarriage and delivery) were compared to treatment. Poor neonatal outcome was a composite measure for pregnancies sustained to 28 weeks or more of gestation ending in stillbirth, preterm birth, or delivery of a growth restricted or low birth weight newborn. RESULTS: There were 26 women in the fever cohort. MT and ST were clinically indistinguishable apart from two ST patients with eschars. FCTs (median [range] hours) were 25 [16–42] for azithromycin (n = 5), 34 [20–53] for antimalarials (n = 5) and 92 [6–260] for other antibiotics/supportive therapy (n = 16). There were 36.4% (8/22) with a poor neonatal outcome. In 18 years, 97 pregnancies were collated, 82 with known outcomes, including two maternal deaths. Proportions of miscarriage 17.3% (14/81) and poor neonatal outcomes 41.8% (28/67) were high, increasing with longer FCTs (p = 0.050, linear trend). Use of azithromycin was not significantly associated with improved neonatal outcomes (p = 0.610) CONCLUSION: The published ST and MT world literature amounts to less than 100 pregnancies due to under recognition and under diagnosis. Evidence supporting the most commonly used treatment, azithromycin, is weak. Collaborative, prospective clinical trials in pregnant women are urgently required to reduce the burden of adverse maternal and newborn outcomes and to determine the safety and efficacy of antimicrobial treatment.